KESIAPAN GURU TK DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA DI TK ISLAM BRAJA INDAH - Fitriyah; Elly Purwanti; sitikhomsiyati; Rahmat Hidayat (AZZAHRA, 2023)
Abstrac This research is motivated by the government's policy regarding Freedom of Learning which is the first step to create a new education, to realize Human Resources (HR) with project-based learning to develop students' abilities, talents, interests and character according to the Pancasila Student Profile. The purpose of this research is to find out and describe the readiness of Kindergarten Teachers in implementing the Independent Curriculum in the learning process and to provide socialization to parents of students regarding the Independent Curriculum. This research uses a qualitative descriptive research type. Qualitative descriptive research is research that seeks to describe, examine and link the data obtained either textually or contextually into writing to gain clarity on the issues discussed. The results of this study as a whole teachers in Braja Indah Islamic Kindergarten are ready to implement the Merdeka Curriculum. Teachers can already create teaching material modules and use appropriate media. The teachers at the Braja Indah Islamic Kindergarten are ready to implement the independent curriculum, by continuing to update their knowledge and have the support of the principal and parents of students. With the existence of an independent curriculum, teachers must continue to learn to update knowledge and learn technology, so that they can provide learning that keeps up with the times.